Change in lateralization of the P22/N30 cortical component of median nerve somatosensory evoked potentials in patients with cervical dystonia after successful treatment with botulinum toxin A - Kanovský, P; Streitová, H; Dufek, J; Znojil, V; Daniel, P; Rektor, I (Movement disorders, 1998)
The precentral P22/N30 cortical component of the median nerve somatosensory evoked potentials (SEPs) was recorded in 16 patients (11 women and five men) suffering from cervical dystonia before and after botulinum toxin therapy. Cervical dystonia was diagnosed as idiopathic in all patients: 13 patients suffered from right-sided torticollis, and three suffered from left-sided torticollis. The amplitude of the P22/N30 component and the side-to-side ratio of amplitude values were measured. Normal values were obtained by acquiring measurements in two groups of healthy volunteers (n1 = 20 and n2 = 20). The recordings in the first control group were done with the patient's head in a normal position, whereas, in the second control group, the patient kept the head intentionally rotated 60 degrees to the right. Patients were treated with local injections of botulinum toxin A (BTX-A). The mean duration of treatment was 8.3 months, and the mean total amount of BTX injected was 295 U. The P22/N30 precentral component was repeatedly recorded in patients after head posture had been corrected to the normal plane by BTX-A treatment. The recordings showed that the amplitude of the P22/N30 precentral component recorded contralaterally to the direction of head deviation was significantly higher in patients before treatment than after treatment. Contralateral pretreatment amplitudes were also significantly higher (p < 0.01 and p < 0.05, respectively) than amplitudes in both groups of healthy volunteers. The mean side-to-side ratio of precentral P22/N30 component amplitudes was significantly higher in patients before treatment compared with after treatment and also compared with both control groups. These changes in dystonic patients probably reflect the direction of head rotation, the muscle pattern of torticollis, and the change in force of dystonic contraction after the treatment. The changes presumably could be the result of higher excitability of the precentral cortex contralateral to head rotation in patients with cervical dystonia and its change after successful BTX-A treatment.
Keywords: botulotoxiny typu A; Male; longitudinální studie; tortikolis; čelní lalok; Dystonia; Adult; Case-Control Studies; dospělí; mužské pohlaví; Electromyography; Median Nerve; Neuromuscular Agents; elektromyografie; Multivariate Analysis; Botulinum Toxins, Type A; nervosvalové látky; dystonie; Frontal Lobe; lidé; ženské pohlaví; studie případů a kontrol; Volition; Humans; nervus medianus; Longitudinal Studies; Torticollis; somatosenzorické evokované potenciály; multivariační analýza; Evoked Potentials, Somatosensory; Female; lidé středního věku; Middle Aged; vůle